Increased waist circumference and prevalence of type 2 diabetes and hypertension in Chinese adults: two population-based cross-sectional surveys in Shanghai, China. Issue 10 (28th October 2013) - Ruan, Ye; Mo, Miao; Joss-Moore, Lisa; Li, Yan Yun; Yang, Qun Di; Shi, Liang; Zhang, Hua; Li, Rui; Xu, Wang Hong
Abstract : Objective: To evaluate the changes in body mass index (BMI) and waist circumference (WC) and their associations with the prevalence of hypertension and type 2 diabetes mellitus (T2DM) in Chinese adults. Design: 2 consecutive population-based cross-sectional surveys. Setting: A total of 12 districts and seven counties in Shanghai, China. Participants: 12 329 randomly selected participants of the survey in 2002–2003, and 7423 randomly selected participants of the survey in 2009. All participants were residents of Shanghai aged 35–74 years. Outcome measures: Measured BMI and WC. Previously diagnosed and newly identified hypertension and T2DM by measured blood pressure, fasting and postload glucose. Results: While the participants of the two surveys were comparable in BMI in each age group, the participants of the 2009 survey had significantly larger WC than those of the 2002–2003 survey, with an annual percentage change being higher among participants aged 45–49 years in men and women. The increase in prevalence of T2DM was observed in all age groups and also appeared more evident in participants aged 45–49 years. The prevalence of hypertension was observed to increase more rapidly in elderly men and middle-aged women. Obesity, both overt and central, was associated with the risk of the two diseases, but BMI was more strongly linked to hypertension while WC appeared more evidently related with T2DM. Conclusions: The prevalence of central obesity and related chronic diseases has been increasing in Shanghai, China. Our findings provide useful information for the projection of the growing burden of T2DM and hypertension in Chinese adults.